Analisis Kebijakan Sistem Pengolahan Air Limbah Rumah Tangga Kota Depok - Melania Hanny Aryantie; Sri Unon Purwati (Jurnal Wilayah dan Lingkungan, 2021)
Study on domestic wastewater management policies is still minimal. Previous research was based on law. This research was conducted to discuss according hierarchy of regulations, then policy analysis under the stakeholders’ understanding. Wastewater management is important because it involves human health and the availability of clean water. The problem in Depok City is untreated domestic wastewater polluting rivers. This condition is caused by the communal Waste Water Treatment Plant (WWTP) that has not been able to reach all settlements and housing. The study aims to conduct a policy analysis of domestic wastewater management to reduce household pollution in Depok. The study was conducted in 2018. Primary data were consisting of perceptions of domestic waste policy makers at regional to national level. Secondary data were previous studies and policy products of Depok City. Qualitative research is determined by the results of content analysis and stakeholder analysis. Primary data obtained through interviews and focus group discussion. The finding is domestic wastewater pollution comes from settlements established before 2012 and settlements that are not served by integrated communal WWTP in Depok City. These conditions can be overcome by building inexpensive and easy to operate domestic wastewater treatment system. The research recommendation is the application of a constructed wetland. The policy implication is adoption of WWTP system in Depok City regulations.